2019
DOI: 10.3866/pku.whxb201802263
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Surfactant-Free Synthesis of Transition Metal/ZnO Nanocomposites for Catalytic Hydrogenation of CO<sub>2</sub> to Methanol

Abstract: Catalytic hydrogenation of CO2 to methanol is an important chemical process owing to its contribution in alleviating the impacts of the greenhouse effect and in realizing the requirement for renewable energy sources. Owing to their excellent synergic functionalities and unique optoelectronic as well as catalytic properties, transition metal/ZnO (M/ZnO) nanocomposites have been widely used as catalysts for this reaction in recent years. Development of size-controlled synthesis of metal/oxide complexes is highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In nanocatalysis, in addition to the metal NPs, semiconductors can be used as supports in order to avoid NP aggregation, facilitate catalyst recovery, provide additional catalytic sites due to metal–support interactions, and facilitate the interaction or activation of substrates or intermediates. However, to our knowledge, few works mentioned the metal–semiconductor heterojunction interactions towards thermal catalysis. Similar to photocatalysis, it has been established in thermal catalysis that semiconductors can contribute to prolong the lifetimes of thermally excited carriers, and potentially boost their catalytic properties …”
Section: Introductionmentioning
confidence: 99%
“…In nanocatalysis, in addition to the metal NPs, semiconductors can be used as supports in order to avoid NP aggregation, facilitate catalyst recovery, provide additional catalytic sites due to metal–support interactions, and facilitate the interaction or activation of substrates or intermediates. However, to our knowledge, few works mentioned the metal–semiconductor heterojunction interactions towards thermal catalysis. Similar to photocatalysis, it has been established in thermal catalysis that semiconductors can contribute to prolong the lifetimes of thermally excited carriers, and potentially boost their catalytic properties …”
Section: Introductionmentioning
confidence: 99%
“…Confirmed by STEM-EDS analysis (Figures 2E and S3F), the covering layer is Al 2 O 3 , which is an indication of SMSI between PtPdCu nanoparticles and the Al 2 O 3 support. 21,30 It has been reported that, after being subjected to thermal treatment, an enhanced metal−support interaction between the nanoparticles and the substrate may take place, which has an effect on catalytic activity. 21,30 Differently, PtPdCu nanoparticles in the PtPdCu-300 catalyst are entirely encapsulated with an Al 2 O 3 overlayer (Figures 2F and S3I), indicating more significant migration of Al 2 O 3 onto the metal surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…21,30 It has been reported that, after being subjected to thermal treatment, an enhanced metal−support interaction between the nanoparticles and the substrate may take place, which has an effect on catalytic activity. 21,30 Differently, PtPdCu nanoparticles in the PtPdCu-300 catalyst are entirely encapsulated with an Al 2 O 3 overlayer (Figures 2F and S3I), indicating more significant migration of Al 2 O 3 onto the metal surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Heterogeneous catalysts for methanol synthesis reactions mainly include Cu-based, noble metal-based (e.g., Au, Ag, Pd, and Pt), and oxide-based catalysts. Among them, Cu-based catalysts hold great potential for practical application due to the advantages of low cost and ideal activity under relatively mild conditions. It is generally believed that the reactivity of Cu catalysts is strongly associated with the use of supports such as ZnO, , ZrO 2 , Al 2 O 3 , and CeO 2 . , The metal oxide supports can regulate the chemical environment of active Cu and the Cu-metal oxide interfaces usually act as active sites for methanol synthesis from CO 2 hydrogenation. Metal–organic frameworks (MOFs) are a new class of porous materials created by the hybrid self-assembly of metal ions, metal clusters, and organic ligands, which have become one of the most striking materials in the field of catalysis, due to their advantages of adjustable pore size, large specific surface area, and high porosity. MOF materials can anchor and confine metal ions/clusters in channels, cages, or defects, and the coordination microenvironment can tailor the chemical state of active metal, thus generating catalytic reactivity .…”
Section: Introductionmentioning
confidence: 99%
“…8−13 Among them, Cu-based catalysts hold great potential for practical application due to the advantages of low cost and ideal activity under relatively mild conditions. It is generally believed that the reactivity of Cu catalysts is strongly associated with the use of supports such as ZnO, 14,15 ZrO 2 , 16−18 Al 2 O 3 , 19 and CeO 2 . 20,21 The metal oxide supports can regulate the chemical environment of active Cu and the Cu-metal oxide interfaces usually act as active sites for methanol synthesis from CO 2 hydrogenation.…”
Section: ■ Introductionmentioning
confidence: 99%